Rückkehr von erfolgreicher Seehundsjagd : [1907] - Hettasch, Paul, 1873-1949. (2001)
Black and white photograph of a group of Inuit men returned from the seal hunt, 1907. Black and white photograph of a group of Inuit men returned from the seal hunt, 1907.